2021
DOI: 10.3390/life11121422
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Hippo Pathway in Rana sylvatica: Yapping Stops in Response to Anoxia

Abstract: Wood frogs (Rana sylvatica) display well-developed anoxia tolerance as one component of their capacity to endure prolonged whole-body freezing during the winter months. Under anoxic conditions, multiple cellular responses are triggered to efficiently cope with stress by suppressing gene transcription and promoting activation of mechanisms that support cell survival. Activation of the Hippo signaling pathway initiates a cascade of protein kinase reactions that end with phosphorylation of YAP protein. Multiple p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Though no studies to date have measured the HS pathway on torpid D. gliroides or any other hibernating mammals, a previous study on the hearts of Rana sylvatica found an overall increase in the HS pathway in response to anoxia exposure. 111 This response was postulated to conserve cellular energy and to function as a cardioprotective/repair mechanism. 111 Thus, HS upregulation may play a similar role in D. gliroides, acting to limit downstream ATP consumption and govern heart size.…”
Section: Hs Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Though no studies to date have measured the HS pathway on torpid D. gliroides or any other hibernating mammals, a previous study on the hearts of Rana sylvatica found an overall increase in the HS pathway in response to anoxia exposure. 111 This response was postulated to conserve cellular energy and to function as a cardioprotective/repair mechanism. 111 Thus, HS upregulation may play a similar role in D. gliroides, acting to limit downstream ATP consumption and govern heart size.…”
Section: Hs Pathwaymentioning
confidence: 99%
“…111 This response was postulated to conserve cellular energy and to function as a cardioprotective/repair mechanism. 111 Thus, HS upregulation may play a similar role in D. gliroides, acting to limit downstream ATP consumption and govern heart size.…”
Section: Hs Pathwaymentioning
confidence: 99%